The effect of flow experience and organizational perspective among academicians in Universiti Teknologi Malaysia - Muhamad, Nor Izzati (2015)
Employee engagement has been receiving much attention in organizations because of its contribution in helping the employees to perform better thus facilitate organizations to grow. However, the complexities in implementing employee engagement require deeper understanding of its origins and practices. This study incorporates the flow experience and organizational perspective (organizational culture and work design) into its framework of study. The purpose of this research is to investigate the effects of flow experience and organizational perspective on employee engagement level. The research employs quantitative approach via survey method. Questionnaires were distributed to a total of 306 academicians in Universiti Teknologi Malaysia (UTM). Statistical analysis shows that the level of engagement, flow experience, organizational culture and work design are moderate among academicians in UTM. Employees' gender and age group show a significant difference in effect towards employee engagement level, while level of education, length of service and academic field have no significance difference on employee engagement. Multiple regression analysis found that flow experience and organizational perspective (organizational culture, work design) have positive effects on employee engagement. Employee engagement is influenced by factors such as employees' enjoyment, total control, concentration, organizational culture, autonomy, task significance and skill variety. The major concerns and challenges in engaging employees are in the work design aspect, specifically task identity and feedback. Since the employee engagement, flow experience, organizational culture and work design are still on the moderate level, current human resource development systems do not put much focus on personal factors and organizational policies for employee engagement to be applied and nurtured. Theoretical contributions from the research suggest the development of a theoretical framework of personal and organizational perspective on employee engagement. This study underlines the essentials of management functions and its contribution in employee engagement among academicians in UTM